Low temperature hydrogenation of pyrolytic lignin over Ru/TiO2: 2D HSQC and 13C NMR study of reactants and products. Issue 1 (22nd October 2015) - Chen, Wen; McClelland, Daniel J.; Azarpira, Ali; Ralph, John; Luo, Zhongyang; Huber, George W.
Abstract : The low temperature hydrogenation of pyrolytic lignin over Ru/TiO2 was studied and characterized with quantitative 13 C and 2D 1 H– 13 C HSQC NMR to determine the changes in carbon functionality. Abstract : Pyrolytic lignin and hydrogenated pyrolytic lignin were characterized by 2D 1 H– 13 C HSQC and quantitative 13 C NMR techniques. The pyrolytic lignin was produced from a mixed maple wood feedstock and separated from the bio-oil by water extraction. p -Hydroxyphenyl (H), guaiacyl (G), and syringyl (S) aromatics were the basic units of pyrolytic lignin. The native lignin β-aryl ether, phenylcoumaran and resinol structures were not present in the pyrolytic lignin. The hydrogenation was conducted with a Ru/TiO2 catalyst at temperatures ranging from 25–150 °C with higher temperatures exhibiting higher levels of hydrogenation. Solid coke formed on the catalyst surface (1% coke yield) even for hydrogenation at 25 °C. The carbon yield of pyrolytic lignin to coke increased from 1% to 5% as the hydrogenation temperature increased from 25 to 150 °C. A single-step hydrogenation at 150 °C resulted in a reduction from 65% to 39% aromatic carbons. A three-step hydrogenation scheme at this same temperature resulted in a reduction of aromatic carbons from 65% to 17%. The decrease in the aromatic carbon corresponded with an increase in the aliphatic carbon. Coke formation reduced from a 5% carbon yield of pyrolytic lignin in the first hydrogenation step to a 1% carbon yield in each of the second and third hydrogenation steps. The pyrolytic lignin could be separated into a high and low molecular weight fraction. The coke yield from the high molecular weight fraction was twice as much as that from the low molecular weight fraction.